2016
DOI: 10.4322/jms.079515
|View full text |Cite
|
Sign up to set email alerts
|

Measurement the “Q” angle through the application of direct method and indirect method

Abstract: Introduction: The “Q” angle is used to measure global alignment of the kneecap, representing the kneecap normal alignment. The average of 15 degrees in ordinary people is accepted as “Q” angle value, 14 degrees for men and 17 degrees for women. Anatomic changes caused by variants produces converging kneecaps or lateral deviation of the tibial tuberosity, changing the “Q” angle value and causing pathologies. Objective: Measure the “Q” angle of asymptomatic people, comparing obtained results. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Mean static knee FPPA (or Q-angle) of collegiate group was 6.9° while club group was 8.1°. Vanzeli, Reis, Pereira, Tavares & Fazan (2016) reported 17° is a normal value for Q-angle for females. Collegiate and club groups in this study showed that their Q-angles were less than 17º.…”
Section: Discussionmentioning
confidence: 98%
“…Mean static knee FPPA (or Q-angle) of collegiate group was 6.9° while club group was 8.1°. Vanzeli, Reis, Pereira, Tavares & Fazan (2016) reported 17° is a normal value for Q-angle for females. Collegiate and club groups in this study showed that their Q-angles were less than 17º.…”
Section: Discussionmentioning
confidence: 98%